Institutional change and economic evolution in regions - Markus Grillitsch (European Regional Science Association (ERSA), 2014)
The overall objective of this paper is to contribute conceptually to the questions why and how regions transform and it joins the debate on economic evolution and institutional change. The paper addresses the challenge of how to conceptualise the interdependencies of institutions of different types and spatial scales. It aims at developing a conceptual framework that i) appreciates the variety of institutional forms and the multi-scalar nature of institutional landscapes, ii) is tangible enough for operationalization in the context of empirical research, and iii) contributes to our understanding about institutional change and economic evolution in regions. The paper offers a review on how institutions have been conceptualised in the context of evolutionary economic geography, a proposal for understanding regional institutional frameworks and institutional change through a novel way of conceptualising institutional layering, a clear distinction between concepts such as agency, networks, social structures and institutional layers, and a discussion about how this can improve our understanding about regional transformation. The concept of institutional layering contributes to the literature on institutional change and institutional complementarity. Important mechanisms and drivers of institutional change within and between institutional layers are discussed. The emphasis in this paper lies on the dynamic interplay between institutional layers. One of the main advantages of the concept of institutional layering is that it illuminates the causality of institutional change. It demands to identify which institutional layer changes how and because of what reason, appreciating also the role of agency and power. In this context, the literature on institutional complementarity underlines the importance of interdependencies between different types of institutions for institutional change as well as economic outcomes. The concept of institutional layering contributes by providing an analytical framework for studying these interdependencies. Furthermore, several mechanisms are identified how the concept of institutional layering contributes to our understanding of regional transformation. The variety and connectedness of institutional layers in a region have an effect on learning and knowledge exchange, the probability to benefit from related variety, the forming of collective interests and resources, the exploration of path plasticity as well as institutional dynamics. Depending on the degree of variety and connectedness of institutional layers, regions will therefore experience differences in the speed of economic evolution, resilience, and the likelihood for continuous or disruptive changes. Using the two dimensions, variety and connectedness of institutional layers, the paper moves towards a typology of regions and relates it to existing empirical literature.
Keywords: B52; O43; 330; Institutions; evolutionary economic geography; geography; regional transformation